A Multifactorial Regulation of Glutathione Metabolism behind Salt Tolerance in Rice - Sara Cimini; Vittoria Locato; Valentina Giacinti; Michela Molinari; Laura De Gara (MDPI AG, 2022)
Knowledge of the stress-induced metabolic alterations in tolerant and sensitive plants is pivotal for identifying interesting traits that improve plant resilience toward unfavorable environmental conditions. This represents a hot topic area of plant science, particularly for crops, due to its implication in food security. Two rice varieties showing dissimilar resistance to salt, Baldo and Vialone Nano, have been studied to investigate the mechanisms underpinning tolerance toward salinity, and these studies have focused on the root system. A detailed analysis of the salt stress-dependent modulation of the redox network is here presented. The different phenotype observed after salt exposure in the two rice varieties is coherent with a differential regulation of cell-cycle progression and cell-death patterns observed at root level. Baldo, the tolerant variety, already showed a highly responsive antioxidative capacity in control conditions. Consistently, stressed Baldo plants showed a different pattern of H2O2 accumulation compared to Vialone Nano. Moreover, glutathione metabolism was finely modulated at transcriptional, post-transcriptional, and post-translational levels in Baldo. These results contribute to highlight the role of ROS and antioxidative pathways as a part of a complex redox network activated in rice toward salt stress.